A Review on Multipurpose Potential of Bioactive Heterocycle Quinoxaline - Chawla, Gita; Gupta, Ojasvi; Pradhan, Tathagata (ChemistrySelect (Weinheim), 2023)
In last few decades, nitrogen‐containing heterocycles have maintained their status as an important core of FDA‐approved drugs and medicinally active compounds. Quinoxaline is one such class of nitrogen‐containing scaffold that has become a subject of extensive research as it possess a plethora of biological activities. Molecular hybridization is a versatile and rational approach to drug design that involves the combination of two bioactive molecules possessing distinct intrinsic activity into a single scaffold for enhancing their therapeutic potential. In view of this, the advancement and potential of quinoxaline hybrids bearing thiazole, triazole, oxadiazole, pyrrolizines, pyrazole, etc. have attracted the keen attention of researchers to explore their therapeutic ability against different biological targets. The present review includes the research in the recent years (2018–2023) and addresses the graceful advancements in the studies related to quinoxaline‐based small molecules including their synthetic routes, biological activities and structure‐activity relationships. We anticipate that this review article will provide comprehensive knowledge of pharmacological importance of quinoxaline analogues and will fulfill the need of scientific community in designing and developing efficacious novel molecules. [+] Both the authors shared equal contribution.The review summarizes the synthetic strategies, SARs and molecular docking of quinoxaline‐based compounds as potential lead for the development of novel small molecules.